Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s13062-016-0129-2
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic protein disorder in histone lysine methylation

Abstract: Histone lysine methyltransferases (HKMTs), catalyze mono-, di- and trimethylation of lysine residues, resulting in a regulatory pattern that controls gene expression. Their involvement in many different cellular processes and diseases makes HKMTs an intensively studied protein group, but scientific interest so far has been concentrated mostly on their catalytic domains. In this work we set out to analyze the structural heterogeneity of human HKMTs and found that many contain long intrinsically disordered regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…The interactions between DFS70/LEDGF and its partners at the IBD appear to be stabilized by intrinsically disordered regions (IDRs). For instance, a disordered IBD-binding short linear motif (IBM) was recently identified in several DFS70/LEDGF interacting partners, with their affinity for IBD binding regulated by phosphorylation of the IBM [45,60,61]. DFS70/LEDGF itself is also an IDR protein, having only two domains that can form stable 3D structures, the PWWP and IBD, which are separated by an IDR (residues 100-345) that lacks welldefined tertiary structure (Fig.…”
Section: Hsp27mentioning
confidence: 99%
“…The interactions between DFS70/LEDGF and its partners at the IBD appear to be stabilized by intrinsically disordered regions (IDRs). For instance, a disordered IBD-binding short linear motif (IBM) was recently identified in several DFS70/LEDGF interacting partners, with their affinity for IBD binding regulated by phosphorylation of the IBM [45,60,61]. DFS70/LEDGF itself is also an IDR protein, having only two domains that can form stable 3D structures, the PWWP and IBD, which are separated by an IDR (residues 100-345) that lacks welldefined tertiary structure (Fig.…”
Section: Hsp27mentioning
confidence: 99%
“…In a previous work [ 26 ] we suggested that the disordered regions of HKMTs may harbor so far unrecognized interaction sites, adding more layers of the regulation of their activity. Based on the observation that many lncRNAs are involved in processes governed by HKMTs, we hypothesized that lncRNA binding might be one of the functions of these regions.…”
Section: Introductionmentioning
confidence: 99%
“…Structural disorder was predicted for all the associated proteins by IUPred [ 23 , 24 ], which is a conservative disorder prediction method showing good correspondence [ 25 ] with the consensus disorder patterns of MobiDB [ 26 ]. The average fraction of disordered residues in the obtained proteomes ranged between 1 and 12 %, with a median of 3.7 % that is extremely low compared to other organisms [ 16 ].…”
Section: Resultsmentioning
confidence: 99%